2022
DOI: 10.1542/peds.2022-056284
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Child Abuse Evaluations During COVID-19: A Multicenter Study

Abstract: BACKGROUND AND OBJECTIVE: The reported impacts of the COVID-19 pandemic on child maltreatment in the United States have been mixed. Encounter trends for child physical abuse within pediatric emergency departments may provide insights. Thus, this study sought to determine the change in the rate of emergency department encounters related to child physical abuse. METHODS: A retrospective study within the Pediatric Emergency Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…25 Of particular concern were mild cases that might have been able to go undetected during periods of decreased health care use and childcare availability during stay-athome orders. 26,27 Although some studies have supported this claim with a reported increase in the severity of abuse presentations during the pandemic 17 or a disproportionate decrease in mild cases, 19 many others have found no difference. [14][15][16]28 The summer of 2021 coincided with all states reopening their economies, mask mandates being lifted, and the liberalization of gathering limits in the US.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Of particular concern were mild cases that might have been able to go undetected during periods of decreased health care use and childcare availability during stay-athome orders. 26,27 Although some studies have supported this claim with a reported increase in the severity of abuse presentations during the pandemic 17 or a disproportionate decrease in mild cases, 19 many others have found no difference. [14][15][16]28 The summer of 2021 coincided with all states reopening their economies, mask mandates being lifted, and the liberalization of gathering limits in the US.…”
Section: Discussionmentioning
confidence: 99%
“…There is no comprehensive method for determining evolving trends in child maltreatment; however, national administrative data sets provide an opportunity to examine larger patterns created by policy or societal changes and may be useful when examining the effects of COVID-19. Although early reports found an increase in physical abuse during the first few months of the pandemic, there have been several multi-institutional studies spanning longer periods that suggest the opposite . There remains a paucity of data regarding the association of the pandemic on more recent trends in physical abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from other sources are mixed; violence and abuse hotlines note general increases in call volume ( De Boer et al, 2021 ; Loiseau et al, 2021 ; Petrowski et al, 2021 ; Rapoport et al, 2021 ), whereas emergency department records show more variation with reports of no changes ( Caron et al, 2022b ; Chaiyachati et al, 2022 ; Russell et al, 2020 ), decreases ( Bullinger et al, 2021b ; Chaiyachati et al, 2022 ; Stivaros et al, 2022 ;), as well as increases in both cases ( Amick et al, 2022 ; Bullinger et al, 2021c ; DeLaroche et al, 2021 ; Kovler et al, 2021 ; Loiseau et al, 2021 ; Sidpra et al, 2021 ), and severity of abuse ( De Boer et al, 2021 ). Several studies have also demonstrated a change in the distribution of types of CM, including dramatic increases in admissions related to neglect or lack of supervision ( Bullinger et al, 2021b ), and admissions related to pediatric abusive head trauma since the pandemic onset ( Sidpra et al, 2021 ).…”
Section: During the Covid-19 Pandemicmentioning
confidence: 99%
“…Early reports described an uptick in AHT and other forms of serious physical abuse, fueling fears that these cases were canaries in the pandemic coal mine . Subsequent research, however, has largely identified either no change or a reduction in the incidence of—if not the severity of—physical abuse diagnosed in hospital settings . While a complete understanding of the patterns and severity of child abuse over the course of the COVID-19 pandemic will continue to evolve in the coming years, evidence for the anticipated shadow pandemic of child abuse, including AHT, has not emerged.…”
mentioning
confidence: 99%